Representasi Konflik Agraria dalam Film Ben dan Jody - Ritonga, Aulia Rahma; Lestari Dara Cinta Utami (Jurnal Kajian Agraria dan Kedaulatan Pangan (JKAKP), 2023)
Film is a medium of communication that has a fairly strong role in constructing and directing the minds of its audience towards the meaning or messages that are constructed. The messages that are built are usually packaged in such a way, through realistic depictions, so as to bring the audience into a real visual representation space. This film aims to see how the agrarian conflict is represented through the film Ben and Jody. The method used in this study is textual analysis using a constructionist approach. The research data were obtained through observing images (visual images) and sound/dialogue (audio) which contained text. The results of the study show that Ben and Jody's film packs a narrative message through the construction of an inland village set, with natural shooting, proper color selection, and a moderate score. Narrative and visual packaging like this is also able to bring the audience into the conflict that Ben and Jody are going through, so that they feel that the conflict is increasingly real in the dynamics of agrarian conflicts in Indonesia. The film Ben & Jody presents a number of discussions about agrarian conflicts, injustice or the incompetence of law enforcers, activism, thuggery, to the serious resistance of grassroots groups. However, what is interesting about them (local citizen actors) can never be described as actors who are able to speak powerfully, because they are often muted by dominant groups (corporations). This film also shows very clearly that customary issues and land disputes are problems that are not easy to resolve. Even now, this problem has not been completely resolved